Obesity associated adipocytokines in girls with premature thelarche - Ilhan, Nevin; Çetin, Dilek (OrtadogÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2016)
Objective: Premature thelarche is defined as the onset of breast development without any additional signs of sexual maturation in girls younger than eight years. In recent years, obesity, hormone-based foods intake, environmental/social change are proposed to play a role in early puberty and the signs of puberty at an early age. The aim of the present study was to evaluate in terms of adipocytokines associated with obesity in premature telarche, which is exact pathophysiology of the disease is still unknown. Material and Methods: The patient group included 19 girls aged between three-eight years who presented to the outpatient clinic of pediatric endocrinology unit with a complaint of unusual breast development. The control group consisted of 17 age-matched healthy girls. Body mass index was calculated according to Turkish reference values (BMISDS) and breast development was evaluated according to the Tanner staging. Follicle stimulating hormone (FSH), luteinising hormone (LH), estradiol (E2) levels were measured by immunochemiluminometric assay and leptin, adiponectin, nesfatin-1, apelin-36, TNF-? and resistin, obesity associated adipose tissue adipocytokines, were measured by ELISA. Results: While the E2 and LH levels in the patient and control groups did not show statistically significant differences, FSH levels were higher in the patient group. When compared to the control group, significant decreases serum leptin and resistin levels, significant increases in apelin-36 and nesfatin-1 levels were found in the patient group. Tumor necrosis factor-alpha (TNF-?) and adiponectin levels did not differ significantly between the groups. Conclusion: As a result, there are several factors, newly identified hormone and signaling molecules, effective on the pathophysiology of the disease known outside the classical hormonal control in premature telarche. However, we would like to emphasize that more detailed studies are needed to determine a better understanding about the main mechanism responsible for the disease. Copyright © 2016 by Tür ki ye Kli nik le ri.
Prematür Telarşli Çocuklarda Obezite İlişkili Adipositokinler
Keywords: Adiponectin; Breast; Growth and development; Leptin; Tumor necrosis factor-alpha